1997
DOI: 10.1136/fn.76.2.f101
|View full text |Cite
|
Sign up to set email alerts
|

Early administration of Bifidobacterium breve to preterm infants: randomised controlled trial

Abstract: Aim-To investigate the colonisation with Bifidobacterium breve of the bowels of very low birthweight (VLBW) infants. Methods-The adverse eVects of B breve were examined in 66 VLBW infants (preliminary study). A prospective randomised clinical study of 91 VLBW infants was also completed and these infants were followed up for three years. Precise viable bacterial counts of serial stool specimens were examined for the first eight weeks after birth in 10 infants. The colonisation rates of administered bacteria wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
243
1
8

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(262 citation statements)
references
References 21 publications
(15 reference statements)
10
243
1
8
Order By: Relevance
“…A randomized controlled trial found that infants whose feed was supplemented with Bifidobacterium breve had higher rates of fecal bifidobacterial colonization at 2 weeks of age (73 vs 12%), improved weight gain and had feeding tolerance. However, the incidence and severity of NEC were not reported in this study (Kitajima et al, 1997). Lin et al (2005) reported a decrease in NEC, NEC plus mortality and severity of NEC, following probiotics L. acidophilus and B. infantis (Infloran), prophylaxis in a prospective, randomized blinded study.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial found that infants whose feed was supplemented with Bifidobacterium breve had higher rates of fecal bifidobacterial colonization at 2 weeks of age (73 vs 12%), improved weight gain and had feeding tolerance. However, the incidence and severity of NEC were not reported in this study (Kitajima et al, 1997). Lin et al (2005) reported a decrease in NEC, NEC plus mortality and severity of NEC, following probiotics L. acidophilus and B. infantis (Infloran), prophylaxis in a prospective, randomized blinded study.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, no lesions were found in germ-free quails associated with Bi®dobacterium infantis-longum or in quails associated with the faecal micro¯ora, containing bi®dobacteria and no clostridia, taken from the healthy neonate twin of the NEC patient. Further studies have shown that bi®dobacteria may have a protective role against NEC, to the extent that inoculation of premature babies with B. breve stabilized the gut micro¯ora, increased weight gain in infants of very low birth weight and resulted in a reduction in gastric aspirated air volume (Kitajima et al 1997).…”
Section: Neonatal Necrotising Enterocolitismentioning
confidence: 99%
“…(Table 1) A randomized controlled trial found that infants whose feed was supplemented with Bifidobacterium breve had higher rates of fecal bifidobacterial colonization at 2 weeks of age (73 vs. 12 %), improved weight gain and had feeding tolerance. However, the incidence and severity of NEC were not reported in this study (39).…”
Section: Probiotic Prophylaxis In Necmentioning
confidence: 53%